Morphodynamic signatures of braiding mechanisms as expressed through change in sediment storage in a gravel‐bed river. Issue 2 (22nd May 2013) - Wheaton, Joseph M.; Brasington, James; Darby, Stephen E.; Kasprak, Alan; Sear, David; Vericat, Damiá
Abstract: [1] Previous flume‐based research on braided channels has revealed four classic mechanisms that produce braiding: central bar development, chute cutoff, lobe dissection, and transverse bar conversion. The importance of these braiding mechanisms relative to other morphodynamic mechanisms in shaping braided rivers has not yet been investigated in the field. Here we exploit repeat topographic surveys of the braided River Feshie (UK) to explore the morphodynamic signatures of different mechanisms of change in sediment storage. Our results indicate that, when combined, the four classic braiding mechanisms do indeed account for the majority of volumetric change in storage in the study reach (61% total). Chute cutoff, traditionally thought of as an erosional braiding mechanism, appears to be the most common braiding mechanism in the study river, but was more the result of deposition during the construction of diagonal bars than it was the erosion of the chute. Three of the four classic mechanisms appeared to be largely net aggradational in nature, whereas secondary mechanisms (including bank erosion, channel incision, and bar sculpting) were primarily net erosional. Although the role of readily erodible banks in facilitating braiding is often conceptualized, we show that bank erosion is as or more important a mechanism in changes in sediment storage than most of the braiding mechanisms, and is the most important "secondary" mechanism (17% of total change). The results of this study provide one of the first field tests of the relative importance of braiding mechanisms observed in flume settings. Key Points: Dynamism of braided rivers explained by quantifying change in sediment storage Dominant morphodynamic signatures were braiding mechanisms and aggradational Study provides first empirical evidence of braiding mechanisms found in flumes